Kinerja Karyawan Dilihat Dari Motivasi Kerja Departemen Housekeeping Di Hotel The Stone Legian Bali Autograph Collection - Erapartiwi , Kadek Oka; Susila, I Made Gede Darma; Wijayanti, Anak Agung Ratih; Subadra, I Nengah (Universitas Triatma Mulya, 2024)
The growth of the tourism industry worldwide is increasing followed by the growth of the hotel industry. Hotel management can develop effective strategies to enhance performance and maintain competitive advantages by considering both intrinsic and extrinsic motivation of their employees. This study aims to examine and obtain empirical evidence of the influence of intrinsic and extrinsic motivation on employee performance in the Housekeeping Department at The Stone Legian Bali Autograph Collection Hotel. The research was conducted at The Stone Legian Bali Autograph Collection Hotel with a sample of 88 employees. The sampling technique used in this study was the census method. Data collection was done through distributing questionnaires using a Likert scale with scores ranging from 1 to 5. The data analysis technique employed in this research was multiple linear regression analysis. The results of this study indicate that Intrinsic Motivation (X1) and Extrinsic Motivation (X2), partially has a positive and significant effect on Employee Performance (Y). Simultaneously, both Intrinsic Motivation (X1) and Extrinsic Motivation (X2) have a positive and significant impact on Employee Performance (Y). Future research is expected to explore additional factors beyond those considered in this study that may influence employee performance.